Inactivation of Foodborne Bacteria Biofilms by Aqueous and Gaseous Ozone - Marino, Marilena; Maifreni, Michela; Baggio, Anna; Innocente, Nadia (Frontiers in Microbiology, 2018)
In this study, the efficacy of treatments with ozone in water and gaseous ozone against attached cells and microbial biofilms of three foodborne species, Pseudomonas fluorescens, Staphylococcus aureus and Listeria monocytogenes was investigated. Biofilms formed on AISI 304 stainless steel coupons from a mixture of three strains (one reference and two wild strains) of each microbial species were subjected to three types of treatment for increasing times: (i) ozonized water (0.5 ppm) by immersion in static condition, (ii) ozonized water under flow conditions, and (iii) gaseous ozone at different concentrations (0.1-20 ppm). The Excel add-in GinaFit tool allowed to estimate the survival curves of attached cells and microbial biofilms, highlighting that, regardless of the treatment, the antimicrobial effect occurred in the first minutes of treatment, while by increasing contact times probably the residual biofilm population acquired greater resistance to ozonation. Treatment with aqueous ozone under static conditions resulted in an estimated viability reduction of 1.61-2.14 Log CFU/cm2 after 20 min, while reduction values were higher (3.26-5.23 Log CFU/cm2) for biofilms treated in dynamic conditions. S. aureus was the most sensitive species to aqueous ozone under dynamic conditions. With regard to the use of gaseous ozone, at low concentrations (up to 0.2 ppm), estimated inactivations of 2.01-2.46 Log CFU/cm2 were obtained after 60 min, while at the highest concentrations a complete inactivation (<10 CFU/cm2) of the biofilms of L. monocytogenes and the reduction of 5.51 and 4.72 Log CFU/cm2 of P. fluorescens and S. aureus respectively after 60 min and 20 min were achieved. Considering the results, ozone in water form might be used in daily sanitation protocols at the end of the day or during process downtime, while gaseous ozone might be used for the treatment of confined spaces for longer times (e.g. overnight) and in the absence of personnel, to allow an eco-friendly control of microbial biofilms and consequently reduce the risk of cross-contamination in the food industry.